Rancang Bangun Trainer Instalasi Listrik Tenaga Sebagai Media Pendukung Praktikum Bengkel Teknologi Listrik Di Politeknik Negeri Ketapang - Yuniar, Nia; Rozie, Fachrul; Chandra, Yudi (entries, 2024)
Practical media is a means to demonstrate an experiment in practicum courses, especially about controlling electric motors and controlling electric motors. Researchers conducted this research to facilitate students in understanding the star delta circuit. The 3phase induction motor is the main tool that uses electrical energy to use electrical energy to drive electrical machines. This motor is the most widely used alternating current motor in the industrial world. Star relationships in motors are needed to minimize current. After the current drops move to delta relationship to get full voltage. In the process of designing this starting circuit trainer is problem identification, data collection, tool design, making trainer components, trials, discussion and conclusions. In the process of designing this starting circuit trainer, select the components needed, then calculate the components needed. After the components are known types and specifications, then the calculation of the starting circuit trainer is made to find out the recommended Rancangan Anggaran Biaya (RAB) on this star delta circuit trainer. The results of the calculation of the capacity of the required components, then this practicum tool can not only be used for star delta circuits or relationships but can be used for other circuits. Practical tools should be used as learning media for Electrical Power Installation practicum courses. For other researchers if they want to develop this tool, they can carry out other methods of both designing the shape and assembly in order to produce a better practicum tool. Keywords: Controller, Controller, Star Delta, Trainer.